Coev-web: a web platform designed to simulate and evaluate coevolving positions along a phylogenetic tree. Issue 1 (December 2015) - Dib, Linda; Meyer, Xavier; Artimo, Panu; Ioannidis, Vassilios; Stockinger, Heinz; Salamin, Nicolas
Abstract Background Available methods to simulate nucleotide or amino acid data typically use Markov models to simulate each position independently. These approaches are not appropriate to assess the performance of combinatorial and probabilistic methods that look for coevolving positions in nucleotide or amino acid sequences. Results We have developed a web-based platform that gives a user-friendly access to two phylogenetic-based methods implementing theCoev model: the evaluation of coevolving scores and the simulation of coevolving positions. We have also extended the capabilities of theCoev model to allow for the generalization of the alphabet used in the Markov model, which can now analyse both nucleotide and amino acid data sets. The simulation of coevolving positions is novel and builds upon the developments of theCoev model. It allows user to simulate pairs of dependent nucleotide or amino acid positions. Conclusions The main focus of our paper is the new simulation method we present for coevolving positions. The implementation of this method is embedded within the web platformCoev-web that is freely accessible athttp://coev.vital-it.ch/, and was tested in most modern web browsers.